Penguatan Manajemen Peternak melalui Diversifikasi Olahan Susu Zero Waste untuk Mendukung Ketahanan Pangan Lokal - Rusdin, Rista Astari; Ardat, Muh. Achyar; Kining, Ekajayanti (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This community service program aims to enhance the economic value of fresh milk through product diversification and the application of zero-waste principles among dairy farmer groups in Enrekang Regency. The implementation methods included training in the production of yogurt, ice cream, and pasteurized milk; mentoring on the implementation of GMP–SSOP and Good Processed Milk Production (CPMB); as well as education in branding and digital marketing. The program adopted a participatory approach, practice-based training, and the integration of appropriate technology within an action-based empowerment framework. The results demonstrated an improvement in partners’ technical skills, expanding their production capacity from traditional dangke to four high-value dairy products. Food safety implementation increased from 42% to 91%. The partners’ monthly revenue rose from IDR 2,500,000 to IDR 3,800,000, accompanied by market expansion and activation of digital sales channels. Additionally, the utilization of whey waste as a raw material for ice cream production supported greater production efficiency. These findings indicate that an integrated approach can sustainably strengthen micro-enterprises based on local livestock resources.